HERPES ZOSTER AFTER COVID VACCINATION - Zanoni, Rodrigo Daniel; Silveira, Zenaide Paulo; Freitas, Lorran Miranda Andrade de; Rocha, Mari Nei Clososki da; Soares, Andre Luiz Faleiro; Oliveira, Maria Emilia Barbosa de; Azevedo, Letícia Maia; Maslinkiewicz, Alexandre; Costa, Ana Carolina Messias de Souza Ferreira da (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Vaccination is an important intervention in preventing the spread of coronavirus (SARS-CoV-2). Messenger RNA vaccines were the first to be commercialized, although cutaneous adverse events have been reported in clinical trials for both vaccines, they have not been well characterized. Given the above, the study aims to report cases of herpes zoster after coronvirus vaccination. This is an integrative literature review carried out using the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. of the following Health Sciences Descriptors (DeCS): “herpes zoster”, “vaccination” and “coronavirus”. Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last ten years (2012-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. Four variables emerged to be studied. Herpesvirus co-infection was present in 45% of positive SARS-CoV-2 cases in moderate to critical clinical status, with EBV and HHV-6 being the most prevalent co-infection, especially in cases of immunosuppression, which may contribute to the worsening of the condition clinical.